A novel information criterion to elucidate a drug delivery mechanism from poly (acrylamide-co-2-hydroxyethyl methacrylate) reinforced with hydroxyapatite composite. (5th December 2018) - Couce, Jomarien García; Campos, Yaima; Torres, Susana; Fuentes, Gastón; Peón, Eduardo; Almirall, Amisel; Delgado, José Ángel; Rodríguez-Cabello, José C.; Cruz Ricondo, Luis J.
Abstract: Hydrophilic composites of poly (acrylamide-co-2-hydroxyethyl methacrylate) reinforced with hydroxyapatite were synthesized, characterized and evaluated as drug delivery systems. The results show a strong dependence of the polymer composition, the degree of crosslinking and the homogeneity of the particles dispersion (filler or the mixed drug) in the characteristics that were analyzed. The mechanical properties were better while the swelling and the diffusion coefficient were worse than hydrogels with cefazolin of similar compositions. A new information criterion based on Bayesian criteria was used to elucidate the best fit. The drug diffusion into the medium was anomalous with more tendency to diffusional transport, indicating that under certain conditions zero-order diffusion could be achieved. This fact suggests that these materials could be used in the manufacture of medical devices for the controlled delivery of drugs and active or biological principles, significantly improving therapeutic procedures today. Graphical abstract: Highlights: Hydroxyapatite-acrylic composites were designed to be used as drug release system. Incorporation of filler decrease the swelling and increase the mechanical properties. Swelling and release are mainly controlled by anomalous diffusion. The composite release 3 times more cephazolin than necessary in a plasma serum. The new information criterion should be very useful to take decisions during the work.